Inheritance as an alteration of property law - Váchová, Aneta (2014)
Subject of the Bachelor thesis "Inheritance as an alteration of property law" is dedicated to the most significant changes, in the area of inheritance law, which were brought about by the implementation of the new Civil Code. In the theoretical part, the principles and general preconditions that have to be met in order to affirm the applicability of the inheritance law are first presented. The goal is to follow the historical development of this law in our territory, from Roman law up until today. A special focus is placed on a juxtaposition of the differences between the antecedent and new Civil Code. The practical part deals with the analysis and evaluation of the most prominent changes and their impact on the legal process of inheritance.